Hubungan Pemberdayaan Suami dan Keluarga dengan Kepatuhan Melaksanakan ANC Pada Ibu Hamil di Puskesmas Pasar Rebo - Febi Puji Utami; Diyah Chadaryanti (Jurnal Ilmiah Kesehatan)
Background : Pregnancy is a very meaningful experience for women. Examination and supervision of pregnant women really needs to be carried out regularly. This aims to prepare the mother and child as optimally as possible physically and mentally during pregnancy, childbirth and postpartum so that a healthy mother and child are obtained. For pregnant women who have never been pregnant or given birth before (primigravida), pregnancy or childbirth is something foreign to them. This is because it is something new he has experienced. Family support, especially husbands, greatly influences antenatal care (ANC) visits for primigravida mothers. Family support is able to motivate primigravida mothers to visit antenatal care. Antenatal care is a pregnancy examination carried out on pregnant women during their pregnancy to prevent complications during pregnancy and to prepare for a healthy birth.